2015
DOI: 10.1111/zoj.12267
|View full text |Cite
|
Sign up to set email alerts
|

A review of the systematics and taxonomy of Pythonidae: an ancient serpent lineage

Abstract: Here we review research over the past quarter century regarding the systematics and taxonomy of an ancient, popular and economically valuable group of snakes referred to as pythons (Serpentes, Pythonidae). All recent phylogenetic studies recognize the pythons as monophyletic; however, the phylogenetic relationships at supraspecific levels are conflicting, and many of the relationships recovered are paraphyletic. We identify several taxonomic changes as necessary to clarify supraspecific relationships and which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 61 publications
0
15
0
2
Order By: Relevance
“…They exhibit their maximum taxonomic, phenotypic, and ecological diversity in the Australasian region (Barker et al. ). Several aspects of this family make them an excellent model for the study of morphological diversity, adaptation, and allometry.…”
mentioning
confidence: 99%
“…They exhibit their maximum taxonomic, phenotypic, and ecological diversity in the Australasian region (Barker et al. ). Several aspects of this family make them an excellent model for the study of morphological diversity, adaptation, and allometry.…”
mentioning
confidence: 99%
“…The Pythonidae is divided between two primary phylogenetic clades, an Afro-Asian clade with two major lineages and an Indo-Australian clade with eight major lineages (Reynolds et al 2014; for recent review, see Barker et al 2015). The two species with confirmed facultative thermogenesis are in the different clades-P. molurus within the Afro-Asian group and M. spilota within the Indo-Australian group.…”
Section: Introductionmentioning
confidence: 98%
“…Pythons are ectothermic throughout most of life, but during brooding the females of some species are known to increase their metabolic rate and exhibit muscular twitching, termed facultative thermogenesis. While widely accepted as a trait of pythons in general, of the 44 extant python species (Barker et al 2015), facultative thermogenesis has been confirmed in only two species: the Burmese python (Python molurus) (Vinegar et al 1970), which has since been broken into two species (P. molurus and P. bivitattus, Jacobs et al 2009) and two subspecies of the carpet python (Morelia spilota spilota) (Slip and Shine 1988); (M. s. imbricata) (Pearson et al 2003). In Abstract Facultative thermogenesis is often attributed to pythons in general despite limited comparative data available for the family.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using multilocus data reported high levels of incomplete lineage sorting, hampering the estimation of species trees (e.g., Pollard et al 2006, Willis et al 2007, Kutschera et al 2014, Barker et al 2015. So, along with reticulation, incomplete lineage sorting results in a deviation from a tree-like depiction of evolutionary histories in a species tree.…”
mentioning
confidence: 99%